Mapping The Scientific Landscape of Follow the Money Approach in Fraud Detection: Bibliometric Analysis Using Watase Uake - Syahrudin, Muhammad (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
This study aims to map the scientific landscape of the